Foster child - Mendoza, Brillamte ([Manila] Seiko Films, Inc., 2007)
A drama centered on the state of foster care in the Philippines.
DVD
Cherry Pie Picache, Jiro Manio, Eugene Domingo
Keywords: Foster Care--Philippines.; Feature Films